2014
DOI: 10.1007/s10533-014-0019-6
|View full text |Cite
|
Sign up to set email alerts
|

N2-fixation by methanotrophs sustains carbon and nitrogen accumulation in pristine peatlands

Abstract: Symbiotic relationships between N 2 -fixing prokaryotes and their autotrophic hosts are essential in nitrogen (N)-limited ecosystems, yet the importance of this association in pristine boreal peatlands, which store 25 % of the world's soil (C), has been overlooked. External inputs of N to bogs are predominantly atmospheric, and given that regions of boreal Canada anchor some of the lowest rates found globally (*1 kg N ha -1 year -1), biomass production is thought to be limited primarily by N. Despite historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
196
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 145 publications
(215 citation statements)
references
References 44 publications
17
196
2
Order By: Relevance
“…If we assume that N:P for preindustrial atmospheric deposition is 10:1 (rounded average of dust - Lawrence and Neff, 2009;vegetation and litter -Wang et al, 2015; forest fire smoke - Zhang et al, 2002), then based on the long-term mean atmospheric P loading calculated above we can expect 0.38 gN m −2-year −1 from atmosphere. This leaves 0.8 g m −2 year −1 to be supplied through biological N fixation, rather lower than has been measured in Alberta peat bogs (Vile et al, 2014;1.7 to 3.4 g m − 2 year − 1 ). If denitrification was active in peat bogs prior to modern N deposition, then our estimate for average long-term N fixation would be proportionately higher.…”
Section: Long-term Peat Nutrient Budgetsmentioning
confidence: 59%
See 1 more Smart Citation
“…If we assume that N:P for preindustrial atmospheric deposition is 10:1 (rounded average of dust - Lawrence and Neff, 2009;vegetation and litter -Wang et al, 2015; forest fire smoke - Zhang et al, 2002), then based on the long-term mean atmospheric P loading calculated above we can expect 0.38 gN m −2-year −1 from atmosphere. This leaves 0.8 g m −2 year −1 to be supplied through biological N fixation, rather lower than has been measured in Alberta peat bogs (Vile et al, 2014;1.7 to 3.4 g m − 2 year − 1 ). If denitrification was active in peat bogs prior to modern N deposition, then our estimate for average long-term N fixation would be proportionately higher.…”
Section: Long-term Peat Nutrient Budgetsmentioning
confidence: 59%
“…As with P, plant cycling has been shown to transport mineralised N to the bog surface (Vile et al, 2014) contributing to surface enrichment. However, it is generally regarded that differences in decay rates of C and N in peat have a greater influence over the N concentration.…”
Section: N and P Enrichment In Surface Peatmentioning
confidence: 99%
“…Therefore, deprivation of methane during the complete experimental phase might have contributed to the observed decrease in N 2 fixation activity. Especially for mosses from the low N-deposition site, where the strongest decrease in N 2 fixation activity was observed, since for similar pristine sites methanotrophic diazotrophs have been shown to contribute to N 2 fixation significantly (Vile et al 2014).…”
Section: Methodsological Considerationsmentioning
confidence: 91%
“…Similarly, along a natural gradient of N deposition levels, the diazotrophic activity (mainly of cyanobacteria) associated with the forest mosses Hylocomium splendens and P. schreberi was shown to decrease with increasing N deposition levels (Leppänen et al 2013). Studies on the effect of N fertilization on S. fuscum and S. angustifolium-associated diazotrophs in a pristine peat bog showed that the diazotrophic activity was negatively affected by high N input, although moss productivity did not change (Vile et al 2014). The difference in response pattern to N deposition between the study of Rousk et al (2013b) and the others indicates that increased N deposition may not have a uniform effect on diazotrophs in all moss species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation